Outcomes of intensive systolic blood pressure reduction in patients with intracerebral hemorrhage and excessively high initial systolic blood pressure: Post Hoc Analysis of a Randomized Clinical Trial - Qureshi, Adnan; Huang, Wei; Lobanova, Iryna; Barsan, William G.; Hanley, Daniel F.; Hsu, Chung Y.; Lin, Cheng-Li; Silbergleit, Robert; Steiner, Thorsten; Suarez, Jose I.; Toyoda, Kazunori; Yamamoto, Haruko (JAMA neurology, 2020)
The safety and efficacy of intensive systolic blood pressure reduction in patients with intracerebral hemorrhage who present with systolic blood pressure greater than 220 mm Hg appears to be unknown.To evaluate the differential outcomes of intensive (goal, 110-139 mm Hg) vs standard (goal, 140-179 mm Hg) systolic blood pressure reduction in patients with intracerebral hemorrhage and initial systolic blood pressure of 220 mm Hg or more vs less than 220 mm Hg.This post hoc analysis of the Antihypertensive Treatment of Acute Cerebral Hemorrhage-II trial was performed in November 2019 on data from the multicenter randomized clinical trial, which was conducted between May 2011 to September 2015. Patients with intracerebral hemorrhage and initial systolic blood pressure of 180 mm Hg or more, randomized within 4.5 hours after symptom onset, were included.Intravenous nicardipine infusion titrated to goals.Neurological deterioration and hematoma expansion within 24 hours and death or severe disability at 90 days, plus kidney adverse events and serious adverse events until day 7 or hospital discharge.A total of 8532 patients were screened, and 999 individuals (mean [SD] age, 62.0 [13.1] years; 620 men [62.0%]) underwent randomization and had an initial SBP value. Among 228 participants with initial systolic blood pressures of 220 mm Hg or more, the rate of neurological deterioration within 24 hours was higher in those who underwent intensive (vs standard) systolic blood pressure reduction (15.5% vs 6.8%; relative risk, 2.28 [95% CI, 1.03-5.07]; P = .04). The rate of death and severe disability (39.0% vs 38.4%; relative risk, 1.02 [95% CI, 0.73-1.78]; P = .92) was not significantly different between the 2 groups. There was a significantly higher rate of kidney adverse events in participants randomized to intensive systolic blood pressure reduction (13.6% vs 4.2%; relative risk, 3.22 [95% CI, 1.21-8.56]; P = .01), but no difference was observed in the rate of kidney serious adverse events.The higher rate of neurological deterioration within 24 hours associated with intensive treatment in patients with intracerebral hemorrhage and initial systolic blood pressure of 220 mm Hg or more, without any benefit in reducing hematoma expansion at 24 hours or death or severe disability at 90 days, warrants caution against generalization of recommendations for intensive systolic blood pressure reduction.